Verizon and Vodafone: a case study in joint ventures - McDonald, Michael (Henry Stewart Talks, 2015)
Introduction to joint ventures, Internal reasons for a joint venture, External reasons for a joint venture, Background on Vodafone & Verizon, The two companies before and after the deal, The future for Verizon and Vodafone